Influence of organizational commitment and employee engagement on employee readiness to change during PT. ABC - Restiani, Tunas; Indiyati, Dian (Goodwood Publishing, 2024)
Purpose: This study aimed to determine how organizational commitment, employee engagement, and readiness change during physical therapy (PT). ABC, and the extent to which organizational commitment and employee engagement influence readiness among PT. ABC partially or simultaneously. Method: This study used a quantitative research method with a causal relationship using a descriptive and verification approach. The study population comprised 452 individuals with PT. ABC. The sampling technique used a simple random sampling method, with the number of samples determined using the Solvin formula, which resulted in 212 respondents. The data collection technique consisted of 49 questions regarding the variables under study. Data analysis was performed using PLS structural equation modeling (SEM). Results: The results show that Employee Engagement has a significant effect on Organizational Commitment and Readiness to Change. The implication of the results of this research is that organizational leaders should maximize Organizational Commitment or Employee Engagement to influence the readiness of individuals in the organization to change direction for better outcomes. Conclusions: This study concludes that enhancing employee engagement and strengthening organizational commitment are essential strategies for increasing readiness for change. Employees with strong emotional bonds and active involvement are more likely to positively embrace transformation. Limitations: This study was limited to PT. ABC focuses only on permanent employees within one organizational context, which restricts the generalizability of the findings. Contribution: This study contributes to organizational behavior research by providing empirical evidence of the role of commitment and engagement in shaping change readiness. Practically, it offers insights for managers to foster engagement and loyalty as mechanisms to ensure a smoother organizational transformation.